Blasphemy in seerat al-nabī,shari’ah and Pakistani Law (A comparative study) - Hidayat Khan,Ihsanullah Chishti, (Seerat Studies, 2024)
Blasphemy is one of the most important and sensitive issue in the discipline of seerat al-nabī, shari’ah and as well as in contemporary criminal law, while it has been recently exploited by the international human rights activists due to its rigorous punishment in Pakistan Penal Code (PPC) on the basis of shari’ah commandments, which is exclusively recommended as death penalty. This issue will be analyzed in the light of Quran and Sunnah along with viewpoints of the prestigious Muslim Jurists and practice of Muslim Ummah from the era of the Prophet (PBUH) till today.